Additively Manufactured Patient Specific Cranioplasty Implants with Antibacterial Properties. Issue 1 (1st May 2022) - Nazeer, Mohamed Nazran; Choo, Hui Leng; Wong, Yin How; Hon, Hui Juen
Abstract: Cranioplasty is the surgical procedure to repair the bone defects in the cranium. Poly(methylmethacrylate) (PMMA) is the most common used biomaterial as it showed better long-term outcomes. Cranioplasty is usually performed through in-situ forming approach. However, the heat and shrinkage and the release of unreacted monomers represent the main drawbacks. Studies also shown a rate of graft infection higher than 10% in surgical PMMA cranioplasty. To overcome these, prefabricating the implants using additive manufacturing (AM) has been proposed. The AM implants could be tailored according to the defect and reduce surgical time, blood loss and the risk of infection. However, the insufficient disinfection of the AM implants may increase the risk of infection. Therefore, the implants can be loaded with antimicrobial agents prior to the cranioplasty. This study synthesised a chemically modified PMMA that can be loaded with antimicrobial agent for AM. The PMMA was sulfonated under different sulfonation temperature, duration, and ratio of PMMA to sulfuric acid. The ionic exchange capacity and degree of sulfonation of the sulfonated PMMA (SPMMA) was determined. In the future, SPMMA with the optimal IEC and DS will be loaded with antimicrobial agent and will be evaluated using the zone of inhibition assay.